2009
DOI: 10.1007/s11096-009-9332-x
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing errors during hospital inpatient care: factors influencing identification by pharmacists

Abstract: Pharmacists routinely identify errors but increasing workload may reduce identification rates. Where resources are limited, they may be better spent on identifying and addressing errors immediately after admission to hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
30
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 27 publications
10
30
0
1
Order By: Relevance
“…Frequency of medication errors in our study was 13.01% that is comparable with results of a large study that have reported 10.5% errors in medication orders [13]. In another study, frequency of medication errors was reported from 33 to 44.6% in critically ill patients [3].…”
Section: Discussionsupporting
confidence: 90%
“…Frequency of medication errors in our study was 13.01% that is comparable with results of a large study that have reported 10.5% errors in medication orders [13]. In another study, frequency of medication errors was reported from 33 to 44.6% in critically ill patients [3].…”
Section: Discussionsupporting
confidence: 90%
“…Six studies (one reported in two papers) used retrospective reviews of disciplinary/performance records to explore performance [38][39][40]61,62,68,71]. Three studies used retrospective analysis of error data [52,53,72], whilst seven studies used prospective data collection techniques on errors [37,42,56,69,70] or clinical interventions [50,64]. Other less common methods used included critical incident technique [52], simulation testing in hypothetical scenarios [65], review of prescription monitoring incidents [41], analysis of claims data [59], videotaping and review of pharmacist performance [46], a controlled study exploring impact of ambient sounds on errors [47], comparison of error rates at different illumination levels [44], root-cause analysis of transcription errors [57], and a literature review (Table 1) [51].…”
Section: Research Methods Usedmentioning
confidence: 99%
“…Of the identified studies, the majority were published in either the USA (n = 15) [43][44][45][46][47][54][55][56]58,59,61,[64][65][66]70], or the UK (n = 14) [37,41,42,[48][49][50]52,53,60,68,69,[71][72][73]. Two studies were conducted in Canada [38][39][40], two in Australia [62,63] and two in Europe [57,67].…”
Section: Country Of Publicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a number of studies, clinical pharmacists have been shown to reduce DRPs in the in-patient settings [11]. Some publications have evaluated the impact of drug errors identified or intercepted by pharmacists in emergency departments [12][13][14], and in in-patient medical and surgical wards [15,16].…”
Section: Introductionmentioning
confidence: 99%